Evaluation of soil parameters for the design of bored piles in residual soils - Harris Mohammed Reza Bin Halim. (2011)
The goal of this project is to provide a better characterization of side and base resistance for the design of bored piles in residual soils. This is done by back analyses of three existing case studies of similar piles in residual soil. The analyses include site investigation result from SPT and CPT as well static pile load test results of the piles. The objective of the back analyses is to determine an appropriate correlation for the ultimate pile shaft capacity and as well for load vs pile head settlement with appropriate semi-empirical formulas available. With the appropriate correlation, a better prediction of the ultimate pile shaft capacity as well the load vs pile head settlement in residual soils will be possible.